2017
DOI: 10.1371/journal.pone.0186405
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide association study using research participants’ self-reported data provides insight into the Th17 and IL-17 pathway

Abstract: A phenome-wide association study of variants in genes in the Th17 and IL-17 pathway was performed using self-reported phenotypes and genetic data from 521,000 research participants of 23andMe. Results replicated known associations with similar effect sizes for autoimmune traits illustrating self-reported traits can be a surrogate for clinically assessed conditions. Novel associations controlling for a false discovery rate of 5% included the association of the variant encoding p.Ile684Ser in TYK2 with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The factors that predispose to these different endotypes remain poorly understood but likely include both genetic and environmental components. Although RORC polymorphisms have not been extensively studied in the context of human asthma, a recent phenome-wide association study revealed an RORC variant associated with protection from allergies (44). A much larger body of evidence clearly shows that the environment can have a profound influence on the development of immune responses in general (45) and asthma in particular (1).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that predispose to these different endotypes remain poorly understood but likely include both genetic and environmental components. Although RORC polymorphisms have not been extensively studied in the context of human asthma, a recent phenome-wide association study revealed an RORC variant associated with protection from allergies (44). A much larger body of evidence clearly shows that the environment can have a profound influence on the development of immune responses in general (45) and asthma in particular (1).…”
Section: Discussionmentioning
confidence: 99%
“…No case has been reported to date where a genetic defect in the IL-17 pathway or an upstream signaling element manifests in detectable Malassezia overgrowth or development of Malassezia-associated skin disorders. Of note, an increased incidence of seborrheic dermatitis was reported as an adverse event accompanying administration of the anti-IL-17A antibody Ixekuzumab (Saeki et al, 2017), and a genetic variant of IL23R was found associated with a decrease in dandruff (Ehm et al, 2017). These observations support a link between the IL-23/IL-17 immune axis and Malassezia in humans.…”
Section: Host Response To the Skin Commensal Yeast Malasseziamentioning
confidence: 69%
“…Support for the contribution of Malassezia-induced IL-17 to disease pathogenesis is further provided by the observation that Malassezia-specific Th17 cells are enriched in AD patients (Balaji et al, 2011;. Beyond AD, a link between the IL-23/IL-17 immune axis and Malassezia-associated disorders has also been proposed in seborrheic dermatitis (Wikramanayake et al, 2018) and dandruff (Ehm et al, 2017). Besides the prominent IL-17 profile, Malassezia-responsive T cells in humans also produce IFN-γ (Balaji et al, 2011;Bacher et al, 2019;, whereby the reason underlying the discrepancy between the two host species remains unclear.…”
Section: Malassezia-induced Immunity and Immunopathology In The Skinmentioning
confidence: 96%
“…In wave 2, we further include 30 variants from the more recent GWAS meta-analyses [29][30][31][32] or variants identified earlier but not prioritized in wave 1 PheWAS. PheWAS approach has been previously applied to BioVU, Vanderbilt's DNA biobank where phenotypes are defined by EMR records namely ICD codes [33], or the 23andMe research database where phenotypes are defined by self-reports [34], or both [35]. It has the potential of validating target, nominating treatment indication and/or assessing safety signal especially if the effect of a genetic variant mimics the pharmacotherapy effect [36].…”
Section: Introductionmentioning
confidence: 99%